Catalyst free-click polymerization: A versatile method for the preparation of soybean oil based poly1, 2, 3-triazoles as coatings with efficient biocidal activity and excellent cytocompatibility. (7th April 2015) - Gholami, Hoshyar; Yeganeh, Hamid; Gharibi, Reza; Jalilian, Mehrdad; Sorayya, Marziyeh
Abstract: Click polymerization was applied for the preparation of soybean oil-based poly1, 2, 3-triazoles (PTAs). Azidated soybean oil (ASBO) was prepared and reacted with two different propyn-functional urethane monomers. Azidated derivatives of a quaternary pyridinium salt (APS) and Cloisite 30B (MMT-N3 ) were also synthesized and tethered into the PTAs to control the physico-mechanical properties as well as biological activities. PTAs showed very good hardness (169–270 s −1 ) and adhesion strength (0.65–1.65 MPa) to Aluminum plate as model substrate. Qualitative and quantitative assessments confirmed promising cytocompatibility of PTAs against fibroblast cells (86–98% viability). Meanwhile, introduction of either APS or MMT-N3 in PTAs induced bactericidal and fungicidal activities against S. aureus, P. aeruginosa and C. albicans . Higher biocidal activity (up to 99% reduction) was detected when these modifiers were used mutually in coatings materials. This work provides a new insight for utilizing a biorenewable material for the preparation of high-performance coatings suitable for biomedical applications. Graphical abstract: Highlights: Efficient utilization of soybean oil as a biorenewable resource raw material. Application of click polymerization for preparation of versatile coatings. Promising antimicrobial activity as well as excellent cytocompatibility. Very good physico-mechanical properties through generation of 1, 2, 3-triazole rings.